Quality of institutions, credit markets and bankruptcy - Christa Hainz (Center for Economic Studies and ifo Institute (CESifo), 2004)
The number of firm bankruptcies is surprisingly low in economies with poor institutions. We study a model of bank-firm relationship and show that the bank's decision to liquidate bad firms has two opposing effects. First, the bank receives a payoff if a firm is liquidated. Second, it loses the rent from incumbent customers that is due to its informational advantage. We show that institutions must improve significantly in order to yield a stable equilibrium in which the optimal number of firms is liquidated. There is also a range where improving institutions may decrease the number of bad firms liquidated.
Keywords: K10; G33; G21; D82; 330; credit markets; institutions; bank competition; information sharing; bankruptcy; relationship banking; Konkurs; Liquidation; Bankgeschäft; Firmenkundengeschäft; Asymmetrische Information; Institutionelle Infrastruktur